A research review of the causes and reasons for the increase in divorce in Muslim society: مسلم معاشرے میں طلاق کے بڑھنے کی وجوہات اور اسباب کا تحقیقی جائزہ - Ahamd, Dr. Mahmood; Ullah, Dr. Muhammad Zia; Muhammad, Sidra Shah (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Understanding the reasons and causes behind the increasing trend of divorce in Muslim societies is crucial for addressing this issue effectively. The prevalence of divorce is influenced by a combination of various factors in these societies. Societal changes, shifting cultural norms, and economic developments play significant roles in this trend. Changes in family structures, financial pressures, and educational advancements contribute to the rising rates of divorce. Furthermore, legal and religious reforms also impact the prevalence of divorce. The expansion of women's rights and educational opportunities has led to increased awareness of divorce rights among women. Legal changes aimed at empowering women and providing them with more rights in divorce proceedings have contributed to this trend. This research provides valuable insights into the different dimensions of Muslim social systems and helps understand the reasons behind the increasing prevalence of divorce. It underscores the importance of addressing societal, cultural, economic, and legal factors to effectively tackle the rising divorce rates in Muslim societies.